2011
DOI: 10.4319/lo.2011.56.4.1411
|View full text |Cite
|
Sign up to set email alerts
|

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron

Abstract: A compilation of more than 30 studies shows that adult Antarctic krill (Euphausia superba) may frequent benthic habitats year-round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2-20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(196 citation statements)
references
References 97 publications
(109 reference statements)
9
175
7
1
Order By: Relevance
“…In contrast, recent feeding data from low latitudes (e.g. South Georgia) with a photoperiod in mid-winter between 8 and 9 h light showed no clear decrease in feeding activity in winter (Schmidt et al 2011a). Teschke et al (2008) and Brown et al (2010) demonstrated that the development of external sexual change of krill is accelerated by photoperiod, although others have shown that the cyclic maturation process is maintained independent of direct control by environmental factors such as food or light (Thomas and Ikeda 1987;Kawaguchi et al 2007).…”
Section: Reduction In Physiological Function In Adultscontrasting
confidence: 40%
See 1 more Smart Citation
“…In contrast, recent feeding data from low latitudes (e.g. South Georgia) with a photoperiod in mid-winter between 8 and 9 h light showed no clear decrease in feeding activity in winter (Schmidt et al 2011a). Teschke et al (2008) and Brown et al (2010) demonstrated that the development of external sexual change of krill is accelerated by photoperiod, although others have shown that the cyclic maturation process is maintained independent of direct control by environmental factors such as food or light (Thomas and Ikeda 1987;Kawaguchi et al 2007).…”
Section: Reduction In Physiological Function In Adultscontrasting
confidence: 40%
“…In winter, krill detected by the Wshery were deeper than 100-200 m depth (Taki et al 2005), and stomach analyses indicated that krill were feeding near or on the bottom (Kawaguchi et al 1986;Ligowski 2000). A recent study found adult krill near the seaXoor in many regions and during all seasons in the Southern Ocean, indicating the ability to utilise benthic detritus to supplement diet throughout the year (Schmidt et al 2011a). …”
Section: Body Lipid and Protein Utilisationmentioning
confidence: 99%
“…The phenomenon that krill can regionally aggregate at unusually deep sites close to the sea floor is known to occur at some sites in the Weddell Sea and around the Antarctic Peninsula. It has been reported from fjords (Grange and Smith, 2013), the shelf (Schmidt et al, 2011) and abyssal depths (Clarke and Tyler, 2008) west of the Antarctic Peninsula and the deep shelf of the southeast Weddell Sea (Gutt and Siegel, 1994). Along the remaining transects, krill has only occurred sporadically and in low numbers.…”
Section: Epibenthos Communitiesmentioning
confidence: 99%
“…It is not clear whether the demographic change observed in our study was the result of segregation, but there are environmental circumstances supporting such segregation. Firstly, subadult males are not sexually active and therefore not dependent on swarming pelagically for reproductive purposes (Hamner et al 1983), secondly, the decrease in subadult males also coincided with the decrease in chlorophyll a and phaeopigment concentrations, indicating that food availability in the upper 50 m of the surface decreased and thirdly, the predation pressure from air breathing predators like Antarctic fur seals and penguins, which are abundant in the area, is highest in the upper 200 m. An interesting possibility is that part of the krill population segregate and go down to the bottom (Schmidt et al 2011), with the possibility of feeding on accumulated phytoplankton (see, e.g., Pape et al 2013) and largely being sheltered from air breathing predators. However, the acoustic recordings did not indicate regular occurrences of krill in particular depth layers which could suggest a systematic segregation of one krill population component relative to others.…”
Section: Discussionmentioning
confidence: 99%
“…Under given circumstances, they drift with the currents as true planktonic organisms and at other times they are able to relocate horizontally, swimming at higher speeds for extended periods of time (Marr 1962;Kanda et al 1982), seemingly unaffected by local currents. They also have a diel vertical migration which may be strong or absent (Hamner and Hamner 2000) and may even use the bottom as a habitat (Schmidt et al 2011). At a small scale, krill are typically distributed in aggregations or swarms believed to facilitate reproduction and feeding; this may also reduce the chance of predation (Hamner et al 1983;Ritz 2000;Evans et al 2007) and/or offer other locomotive energetic advantages (Ritz 2000).…”
Section: Introductionmentioning
confidence: 99%